Graph modeling of Compatible and Incompatible Traffic Streams at Road Intersections (GM-CITSRI) - Baclayo, Kareen T.; Lumpas, Raisa R. (2007)
Graphs are a convenient way of illustrating objects and the connections between them. Structures that can be represented as graphs are ubiquitous, and many problems of practical interest can be represented by graphs. One problem that is of interest to the authors is the Phasing of Traffic Lights Problem (PTLP). PTLP concerns with finding traffic streams at an intersection that are compatible, that is traffic streams can move at the same time witout dangerous consequences. In this study, two types of intersections are dealt with, 3-way and 4-way intersections. These two are the more common types of intersections. Similarly, it is also significant to know corresponding incompatible traffic streams at an intersection. Thus, the goal of this study is to create graph models or representations of both compatible and incompatible traffic streams at road intersections. Graph models of traffic streams are created using two concepts in Graph Theory. A graph of compatible traffic streams is acquired using the concept of a Compatibility Graph, a graph whose vertices represent objects and whose edges join those pairs of vertices which are compatible, that is they are admissible in a given relationship. A graph of the incompatible traffic streams, on the other hand, is obtained by executing a secondary graph operation called Edge-Complement or Complement of the compatibility graph.